The development of health institutions in Turkey (1923 – 1980) - Ameen Abbas Natheer, Ameen Abbas Natheer (Journal of College of Education, 2020)
Health services are a basic human necessity for every citizen in the world, because they are directly linked to his health and life, and therefore has a different strategic importance with other aspects of life, and all governments in the world provide this service without regard to the material cost and the differences between members of society, and health services provided From the State to the Citizens is a leading indicator of social and economic progress throughout the world, including Turkey. In this study, we will try to show the historical development of the reforms in the health sector in Turkey that have been achieved on the ground. A basket of reforms within the framework of the health transformation program and caused significant differences in the financing of health care services. The study also dealt with health services in Turkey and the development of laws and regulations that successive Turkish governments developed to promote the health situation and provide better services to all members of the Turkish community.